Analysis of The Effectiveness of Simpatika Implementation in Madrasah Management at the Ministry of Religious Affairs Pandeglang Regency - Tb Asep Jamaludin Akbar; Hakim, Agus Lukman (Future Science, 2025)
This study aims to analyze the effectiveness of the implementation of the Information System for Educators and Education Personnel (SIMPATIKA) in the management of madrasahs under the Ministry of Religious Affairs in Pandeglang Regency. A qualitative approach was used, with data collected through observations, in-depth interviews, and documentation. The analysis is based on the organizational systems theory by Ivancevich, Konopaske, and Matteson, encompassing four elements: input, process, output, and feedback relationships. The results reveal that while SIMPATIKA holds strategic potential as an educational data management tool, its implementation in Pandeglang has not been effective. There is a 47.3% data gap between the central and local databases, with 62.9% of madrasahs experiencing significant data inconsistencies. Key contributing factors include technological infrastructure limitations, inadequate human resource capacity, and the absence of continuous data validation mechanisms. The study concludes that SIMPATIKA has yet to fully support good governance principles in madrasah management. Strengthening digital capacity, improving validation systems, and enhancing cross-unit collaboration are necessary to achieve effective, transparent, and accountable educational governance.